PENGARUH ORGANIZATIONAL CAPITAL DAN TRANSFER PRICING AGGRESSIVENESS TERHADAP TAX AVOIDANCE - Muhammad Fahri, (2023)
This study was conducted with the aim of obtaining empirical evidence regarding the factors that influence tax avoidance. The independent variables used in this study are organizational capital and transfer pricing aggressiveness. This study also uses control variables, namely leverage and profitability. This research is a type of quantitative research that uses secondary data in the form of annual reports and audited company financial reports. This study tested 273 observation data from 79 manufacturing sector companies on the Indonesia Stock Exchange during 2019-2021. Multiple linear regression test technique is used in this study to test the effect of organizational capital and transfer pricing aggressiveness on tax avoidance. Based on the results of the data analysis that has been presented, this study provides results that organizational capital and transfer pricing aggressiveness have no effect on tax avoidance. The implications of the results of this study focus on improvements in tax regulations and increasing taxpayer awareness to minimize tax avoidance practices.